2016
DOI: 10.1159/000443460
|View full text |Cite
|
Sign up to set email alerts
|

Renalase Secreted by Human Kidney HEK293T Cells Lacks its N-Terminal Peptide: Implications for Putative Mechanisms of Renalase Action

Abstract: Background/Aims: Renalase is a recently discovered flavoprotein involved in regulation of blood pressure. Altered renalase levels have been found in blood of patients with end stage renal disease. The antihypertensive effect of circulating renalase is attributed to putative FAD-dependent monoamine oxidase activity demonstrated by some authors. Being synthesized as an intracellular flavoprotein renalase requires the presence of its N-terminal peptide for FAD accommodation. However, conventional routes of export… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 42 publications
0
12
0
6
Order By: Relevance
“…Данный подход клонирования генов мы использовали при клонировании гена реналазы-1 и -2 [21,22], а также при клонировании различных форм реналазы в плазмидные вектора pET-28 и pcDNA4 (Fedchenko et al, in preparation).…”
Section: Discussionunclassified
“…Данный подход клонирования генов мы использовали при клонировании гена реналазы-1 и -2 [21,22], а также при клонировании различных форм реналазы в плазмидные вектора pET-28 и pcDNA4 (Fedchenko et al, in preparation).…”
Section: Discussionunclassified
“…They also found that human recombinant renalase-1 secreted by HEК293T cells also lacks the N-terminal signal peptide. These results suggest renalase's signal peptide is cleaved upon secretion and that extracellular (blood and urine) renalase acts in a FADindependent manner [24]. However, the possibility of additional proteolytic processing of extracellular renalase should be considered [25].…”
Section: The Mechanism Of Renalase's Cytoprotective Propertiesmentioning
confidence: 98%
“…Renalase is a secretory protein which attracts much attention in the context of blood pressure regulation . It is secreted by the kidney and kidney‐derived cell cultures, and renalase deficiency frequently develops in patients with end‐stage renal disease (ESRD), patients with other chronic renal diseases and related experimental animal models, thus determining development of hypertension complications. There are many reports of altered levels of renalase in biological body fluids (plasma and urine) in these and other groups of patients (or animal models) .…”
Section: Introductionmentioning
confidence: 99%
“…Recently we successfully used mass spectrometry for qualitative detection of renalase in human urine 14,15 and cultivated HEK293T cells. 7 In the case of renalase detection in urine, ammonium sulfate precipitation provided a convenient approach for concentrating full-length renalase up to detectable limits and eliminating possible renalase-derived peptides. 14,15 In the study reported here, we developed a new method for quantitative determination of renalase based on mass spectrometric determination of a proteotypic peptide containing С-terminal…”
Section: Introductionmentioning
confidence: 99%